The importance of quantitative analysis in the study of the topic of solutions - Ibodulloyeva Mavjuda Ibodulloyevna; Sobirova Nazokat Abbos qizi; Alimurodov Muxammad Saydmurot o‘g’li (Genius Journals, 2022)
This article reflects the importance of quantitative analysis in the study of the topic of solutions. Types of solutions based on different methods, methods of their expression are highlighted. The role of quantitative analysis in medicine is also indicated.
Keywords: Solutions; quantitative analysis; nonelectrolytes; electrolytes